Canada's Fiduciary Obligation to Aboriginal Peoples in the Context of Accession to Sovereignty by Quebec, Volume 2: Domestic Dimensions - Dupuis, Renée; McNeil, Kent (Osgoode Digital Commons, 1995)
The Royal Commission on Aboriginal Peoples was established on 26 August 1991 by Order in Council P.C. 1991-1597 with the following mandate: "The Commission of Inquiry should investigate the evolution of the relationship among aboriginal peoples (Indian, Inuit and Métis), the Canadian government, and Canadian society as a whole. It should propose specific solutions, rooted in domestic and international experience, to the problems which have plagued those relationships and which confront aboriginal peoples today. The Commission should examine all issues which it deems to be relevant to any or all of the aboriginal peoples of Canada." (P.C. 1991-1597) https://digitalcommons.osgoode.yorku.ca/faculty_books/1393/thumbnail.jpg